Use of e-book by students: Field study with Masters Students at the Faculty of Humanities and Social Sciences of M’sila University - Abid , nabila; rahal , slimen (Journal of Social Sciences and Humanities, 2021)
The study deals with the use of e-book by students of the second year master at the Faculty of Humanities and Social Sciences at M’sila University. It aims at identifying the reality of the use of e-book by students by knowing the nature of students' uses of e-book. The students will then explore the technological skills needed to deal with the e-book and finally identify the problems and difficulties encountered in the sample study and stand in the way of achieving wider benefits from the e-book and finding appropriate solutions to those difficulties. The nature of the study required reliance on the descriptive approach that we employed through the questionnaire tool as a key data collection tool. After this study, we have reached a number of results, the most important of which is that the second year master students at the Faculty of Humanities and Social Sciences for technological did not have required skills for using e-book and also face technical and health difficulties in using e-book.